Poetry magazines: description of an object - Carlos Battilana (Estudios de Teoría Literaria, 2015)
This article sets out to examine different mechanisms of poetry magazines as objects of reflections per se. Literary magazines have a cartographical quality in the sense that they organize the map of a group of works and authors. A magazine produces a critical system of selection. Far from suggesting a stable nature of literary magazines, each of their interventions influences a concrete community and temporality in different ways, which turns each historical moment into a stimulus whose effects are not known beforehand.